Sharia Hotels in the Perspective of Institutional Economics, Human Resource Management and Entrepreneurship: A Comprehensive Analysis - Suryani, Ni Kadek; Ni Ketut Karwini; Ida Ayu Putu Widani Sugianingrat (Sinergi International Journal of Management and Business, 2025)
This study aims to analyze the implementation of sharia principles in the operation of sharia hotels in Indonesia from the perspective of institutional economics, human resource management, and entrepreneurship. The research methods used are systematic literature review, which include studies from leading academic databases, namely Scopus, Google Scholar, JSTOR, and IEEE Xplore. The main findings of this study indicate that a strong institutional and regulatory structure is essential for the operation of sharia hotels, with government policy support playing a key role in ensuring compliance with sharia principles. In addition, employee training and development that focuses on Islamic values has been shown to improve service quality and customer satisfaction. Entrepreneurship in sharia hotels involves innovation and development of sharia-compliant business models, which helps improve the competitiveness and sustainability of hotels.